The Effectiveness of the Realistic Mathematics Education (RME) Approach on Student Mathematics Learning Outcomes: A Meta-Analysis - Nurdin, Nurdin; Ariska, Mutmainna; Hasma, Elzi Amilia; Anugrah, Dian; Elihami, Elihami (Universitas Muhammadiyah Enrekang, 2025)
This study aims to evaluate the effectiveness of the Realistic Mathematics Education (RME) approach on student mathematics learning outcomes through meta-analysis. A meta-analysis was conducted on 11 articles that met the inclusion criteria, namely using an experimental design with control and experimental groups and reporting quantitative data in the form of mean values, standard deviations, and sample sizes. The results of the analysis showed that 73% of the articles had a very large effect size, 18% had a large effect size, and 9% had a very small effect size. In addition, the results of the two-mean test showed that the mean value of student learning outcomes in the experimental group using the RME approach (78.66) was significantly higher than that of the control group (67.82), with a t-value of 5.605 exceeding the t-table value. These findings indicate that the RME approach is effective in improving students' mathematics learning outcomes. RME makes learning more contextual, meaningful, and relevant to students' daily lives, thereby increasing motivation, active participation, and conceptual understanding. Thus, this approach deserves to be widely applied in mathematics learning at the primary and secondary education levels.